Keterkaitan Dinamika Kelompok dengan Keberhasilan Pola Kemitraan Ayam Ras Pedaging (Kasus Kelompok Kurnia di Kabupaten Bogor) - Wahyuni, Sri (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
The subject of this study is (1) to analyze dynamic level in Kurnia group, (2) to analyze linkage farmers characteristic with the dynamic group in Kurnia group, and (3) to analyze linkage of a dynamic group with successful partnership formula. This study was conducted by a survey in Kurnia Group. Technical sampling was determined by purposive sampling. The respondents were 30 people who had running activities in the group. The result shows that firstly, the Generally dynamic group in Kurnia group dynamic. Dynamic group in Kurnia depend of group aim, group structure, task function, training group etc. Successful in partnership show success, it depends on income (86,7%) dan Productivity (90%). Experience of a farmer has a linkage with the dynamic group. Age of respondents, occupation does not have a linkage with the dynamic group. Generally, there is no linkage of the dynamic group with a successful partnership formula. This indicated that dynamic group does not influence the successful partnership formula.